Analisis Kepuasan Pengguna E-Katalog Dan Kemudahan Penggunaan Terhadap Efektivitas Belanja Barang Di Lingkungan TNI AL - Edvien Adi Putra (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This research aims to investigate user satisfaction and usability of e-catalogs in the context of procurement effectiveness in the Indonesian Navy (TNI AL) environment. Utilizing a qualitative approach and literature review, survey data and in-depth interviews were obtained to analyze challenges and factors affecting e-catalog usage. Findings reveal that the majority of users experience difficulties in using e-catalogs, particularly regarding navigation and user interface complexity. This complexity is associated with inadequate training and lack of clear guidelines. Furthermore, user satisfaction with e-catalogs correlates with usability and availability of adequate information. Thus, simplifying the user interface and enhancing information accessibility are identified as key steps to improve procurement effectiveness in the TNI AL environment.